REVOLUTIONIZING POLLUTION REDUCTION IN THE MARMARA SEA THROUGH INNOVATIVE TECHNOLOGIES - Erkan, Hanife Sari; Cakmakci, Mehmet; Engin, Guleda Onkal (ISTANBUL UNIV PRESS, ISTANBUL UNIV RECTORATE, 2025)
The Marmara Sea, located in northwestern Turkey, faced mucilage formation caused by factors such as excess nutrients, bacteria or algae, and specific physical conditions in 2021. This chapter examines the significance of Istanbul as a point source of pollution in the Marmara Sea due to its large-scale generation of municipal wastewater. Additionally, non-point sources of pollution also contribute significantly to the pollution in the Marmara Sea. However, this paper focuses specifically on evaluating the impact of municipal point sources. To address the pollution problem, it is crucial to replace the existing mechanical treatment facilities with innovative technologies. These advanced treatment approaches offer improved pollutant removal and better control over nutrient levels, thereby reducing the risk of mucilage formation and other pollution-related issues. By adopting these innovative treatment technologies, Istanbul can play a crucial role in combating pollution in the Marmara Sea and protecting its delicate ecosystem.
Keywords: Marmara Sea; mucilage incident; novel treatment technologies; point sources; aerobic granular sludge; membrane bioreactor; WASTE-WATER TREATMENT; NORTHERN ADRIATIC SEA; MEMBRANE BIOREACTORS; REMOVAL; INTEGRATION; PHOSPHORUS; NITROGEN; DENITRIFICATION; PERFORMANCE; Environmental Sciences & Ecology; Marine & Freshwater Biology